Mulberry and its main components protect against oxidized low-density lipoprotein-induced endothelial nitric oxide synthase uncoupling. (February 2017) - Lee, Hwa-Young; Oh, Mi-Ra; Jung, Eun-Soo; Lee, Yang-Soo; Kim, Deok-Su; Kang, Seong-Sun; Chae, Han-Jung; Chae, Soo-Wan
Highlights: Mulberry extract and its components have significant antioxidant activity. Mulberry extract and its components regulate eNOS uncoupling. Mulberry extract and its components regulate NO production. Mulberry extract has the potential to treat vascular endothelial dysfunction. Abstract: Nitric oxide (NO), which is produced by endothelial NO synthase (eNOS), is an important protective molecule in the vasculature. However, eNOS coupling and its resultant activation are altered under oxidative stress. Under these conditions, eNOS uses molecular oxygen as a substrate instead ofl -arginine, resulting in the production of superoxide anion radicals ( O 2 - ) rather than NO. We explored the effects of mulberry extract and its components on eNOS uncoupling induced by oxidized low-density lipoprotein in HUVECs and investigated the potential molecular mechanism. Ox-LDL significantly increased O 2 - production and reduced NO release from HUVECs. Pretreatment of cells with mulberry extract and its main components significantly inhibited ox-LDL-induced O 2 - generation, preserving NO level. Mulberry extract also prevented ox-LDL-induced reduction in phospho-eNOS Thr495. These regulatory effects were related to phosphorylation of eNOS Thr495. Mulberry extract and its components can potentially be used to treat ox-LDL-related vascular endothelial dysfunction.